Perilaku gaya hidup dan obesitas sebagai faktor risiko kejadian diabetes melitus tipe 2 di RSUD. Aji Batara Agung Dewa Sakti Samboja Kabupaten Kutai Kartanegara - Neni Sundari; Fatwa Sari Tetra Dewi; Muhammad Robikhul Ikhsan (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Lifestyle behavior and obesity as risk factors for the occurrence of type 2 diabetes mellitus at RSUD Aji Batara Agung Dewa Sakti Samboja, Kutai KartanegaraPurposeThe aim of this study was to determine the correlation between knowledge of healthy behavior and obesity on the occurrence of type 2 diabetes mellitus.MethodsThis research was an observational-analytical- quantitative study with a case-control design. The study subjects were selected by purposive sampling totaling 212 outpatients and inpatients in the RSUD Aji Batara Agung Desa Sakti in which 106 patients were suffering type 2 diabetes and 106 control patients that were not suffering diabetes mellitus. All subjects were between 25-64 years old.ResultsKnowledge of healthy behavior was not statistically significant in the occurrence of type 2 diabetes mellitus while in the univariable data analysis, central obesity was statistically significant. This finding was closely related to the behavior of low physical inactivity but central obesity increased with age and the prevalence was greater in women. Multivariable analysis showed that central obesity, physical inactivity (moderate physical activity and low activity) and very high incomes were the main risk factors for type 2 diabetes mellitus.ConclusionThe occurrence of type 2 diabetes mellitus in the community needs to be reduced by improving healthy lifestyles, physical activity and patterns of healthy diet, by eating fruits and vegetables, and not drinking alcohol nor smoking.